Analisis Kadar Mangan (Mn) dan Besi (Fe) Pada Instalasi Pengolahan Air Minum (IPA 3) PT Hanarida Tirta Birawa - Nur Oktavia Nikmatin Hasanah; Yayok Suryo Purnomo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Population growth continues to increase, making the need for clean water increasingly increasing. The quality of raw water needed as a source of clean water also requires further processing to ensure it meets quality standards. To make clean water and drinking water suitable for consumption by the community, the role of the Regional Drinking Water Company (PDAM) is needed. PT Hanarida Tirta Birawa is one of the companies that serves clean water needs in Sidoarjo Regency. Clean Water Treatment Plants will have a big impact on environmental quality, especially water. The parameters that have the greatest influence on the content of raw water that will be processed into clean water are Fe (Ferrom/Iron) and Mn (Manganese) contained in raw water. At PT Hanarida Tirta Birawa, the manganese (Mn) content ranges from 0.04 to 0.13 mg/l and iron (Fe) ranges from 0.11 to 0.17 mg/l and meets the quality standards of RI Minister of Health Regulation No. 492/Menkes/PER/IV/2010. The reduction in processed water reached 87.23% for manganese and 93.29% for iron.